Correlation Analysis of Dividend Policies and Stock Prices of Philippine Financial Firms - Bagnol, Nessy Jovanah G.; Bedayo, Daniel E.; Juson, Felicity G.; Montes, Keshia Kaye R.; Semillano, John Kemuel A.; Nicolas, Erika S. (American Journal of Management, 2025)
This study examines the correlation between dividend policies and stock prices of selected financial sector companies in the Philippines. The primary beneficiaries are current and potential stock investors in the Philippine stock market, providing insights for better investment decisions. A descriptive correlational research design was employed, relying solely on secondary data from reliable sources such as PSE Edge, Bloomberg, First Metro Securities, and COL Financial, rather than survey questionnaires or other instruments. Using purposive sampling, the study analyzed publicly listed financial sector companies in the Philippines. To ensure accuracy, credibility, and consistency, pre-existing data from various authors and organizations were used. Statistical tools were applied to examine relationships between dividend yield, dividend coverage ratio, and retention ratio with stock prices, revealing no significant correlation. Additionally, variations in company profile characteristics did not significantly impact dividend policies. However, findings indicate a statistically significant relationship between dividend payout ratio and stock price, as well as differences in payout ratio when grouped by earnings level. All data were handled responsibly throughout the research process.